An Investigation into Non-English Educational Background Lecturers' Competence in Teaching English for Biology - Eko Sulistiono; Indrawati Pusparini; Tities Hijratur Rahmah (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2026)
This research employed a qualitative method. The study was conducted at Insan Budi University. The instruments used to collect data for the research included a questionnaire, interview, and documentation of the language teaching process inside or outside the classroom at the Biology Education Study Program. The researcher employed a qualitative approach, specifically a descriptive qualitative research method, in this study. The research objects are non-English educational background lecturers and biology education students of Insan Budi Utomo University Malang for the 2022–2023 academic year.The research results were as follows: 1) the lecturer with a non-English educational background develops English skills through autodidacts such as reading international journals and learning from material or English content. 2) the strategies applied by the lecturer with a non-English educational background in developing her competencies (pedagogical) in teaching “English for Biology” by reading the international journal to increase knowledge of biology education, participating in national workshops and conferences to increase professional and pedagogical competence, and the lecturer discusses and sharing with another lecturer from English Department to increase personal and social competence. 3) the perceptions of students towards the competencies of the lecturer with a non-English educational background in teaching. The students were very fond of the way the lecturer taught English.The study concludes that English proficiency and a strong set of competencies are crucial for lecturers with non-English backgrounds teaching English. Students' English language skills can improve with effective teaching and motivation.